Biomechanical modeling applied to human movement analysis - Roemer, K. (ISBS - Conference Proceedings Archive (Konstanz), 2010)
Biomechanical modelling can be a helpful instrument in human movement analysis. Here, the focus will be set on analyzing human movement using inverse dynamics. Dealing with inverse problems, one important issue is the transfer of a real motion to the model and how to find an optimal description of the movement. Furthermore, joint models, the description of joint kinematics, as well as the individual adaptability of those models will influence the results of human movement analysis.